A Business Model Incorporating Harmonic Control as a Value-added Service for Utility-owned Electricity Retailers - Li, Kangping; Mu, Qitian; Wang, Fei; Gao, Yajing; Li, Gang; Shafie-khah, Miadreza; Catalão, João P. S.; Yang, Yongchun; Re, Jiafeng (Institute of Electrical and Electronic Engineers, 2019)
With the deepening of electricity market reform in China, the competition in the electricity retail market becomes increasingly intense. Electricity retailers (ERs) need to explore new business models to enhance their competitiveness in the retail market. Meanwhile, with the improvement of industrial production and people's living standards, more and more nonlinear electrical equipment have been put into use, leading to severe harmonic pollution problems. Harmonic pollution causes loss of electricity, resulting in the economic loss of customers, especially for large industrial customers. In the above contexts, this paper proposes a novel business model that incorporates harmonic control as a value-added service into electricity retail contracts for utility-owned ERs. Both utility-owned ERs and customers can benefit from the designed business model. For customers, it helps them to improve the power quality while saving the electricity cost. For ERs, it helps them to cultivate the customer loyalty and improve the customer satisfaction. A case study is performed to demonstrate the effectiveness of the proposed business model.
Keywords: fi=Energiatekniikka|en=Energy Technology|